Fascism [large type] : a warning - Albright, Madeleine Korbel; Woodward, William, 1951- (HarperLuxe, an imprint of HarperCollinsPublishers, 2018)
The former U.S. secretary of state presents a timely, considered, and personal look at the history and current resurgence of fascism and the virulent threat it poses to international freedom, prosperity, and peace.